Pengaruh Nilai Tukar Rupiah dan Suku Bunga Terhadap Return Saham dengan Profitabilitas Sebagai Variabel Intervening Pada Perusahaan Farmasi yang Terdaftar di BEI Tahun 2012-2016 - diky Prasetyo (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
The purpose of this study is to describe (1) the effect of exchange rate variables on profitability, (2) the effect of exchange rate on stock return, (3) interest rate influence on profitability, (4) influence of interest rate on stock return, (5) to stock return, (6) influence of rupiah exchange rate, interest rate to stock return through profitability. The technique used is a census or a total sample with criteria of pharmaceutical companies listed on the Indonesia Stock Exchange (BEI) which presents complete financial statements during the study period (2012-2014). Data analysis techniques use multiple linear regression analysis supported by F test, T test, and determination. The results of this study showed that (1) exchange rate was negative and significant to profitability α = 0,05 (p = 0,009), (2) exchange rate has no significant effect on stock return α = 0,05 (p = 0,131), (3) interest rate has a positive effect on profitability α = 0,005 (p = 0,003), (4) the interest rate has no significant effect on stock return α = 0,05 (p = 0,782), (5) profitability have positive effect on stock return α0,05 (p = 0,003), (6) the rupiah exchange rate against stock return through profitabiltias shows the value (1,965> 1,960), as well as for the result of the interest rate calculation on the stock return through profitabiltias shows (2,108> 1,960).